Moral Mazes: the world of corporate managers (20th anniversary edition) [Robert Jackall] - Henriques, Gabriel (2014)
Recensão do livro Moral Mazes: the world of corporate managers (20th anniversary edition) [Robert Jackall], 2010, Oxford University Press, Nova Iorque